Analisis Efektivitas Penyelenggaraan Program Tol Laut Trayek T-26 Tahun 2024 dalam Menekan Disparitas Harga pada Kabupaten Fakfak, Papua Barat - Rizki Adi Pratama; Dian Junita Arisusanty; Femmy Asdiana; Faris Nofandi; Romanda Annas Amrullah (Pusat riset dan Inovasi Nasional, 2025)
This study aims to evaluate the effectiveness of the Sea Toll Program, specifically Route T-26, with a focus on its outcomes and tangible benefits for the community in Fakfak Regency, West Papua. The research employed a descriptive quantitative method using statistical analysis through a paired sample t-test. Primary data were collected through field observations and interviews with relevant agencies such as the Directorate of Sea Traffic and Transportation and field implementation consultants, while secondary data were sourced from the 2024 operational report of Route T-26. Data collection techniques included field observation, primary surveys, document studies, and secondary data analysis. The findings indicate that the Sea Toll Program contributes to improving logistics distribution, lowering the prices of several key commodities, and reducing household expenditures, although statistical tests showed that the price differences were not significant. The implications highlight the need to optimize the volume and regularity of Sea Toll voyages to strengthen economic resilience in remote, outermost, underdeveloped, and border areas (3TP).